Predicting integrated effects of subsurface drainage and climate change on water balance and nitrate losses - Samira Ziaeifar; Ali Shahidi; Amir-Ashkan Malakshahi; Abdullah Darzi-Naftchali; Mehdi Nadi (Applied Water Science)
Abstract To ensure the continued contribution of agriculture to global food security, food production systems must adapt to the challenges posed by environmental degradation and climate change. This study assesses the potential impacts of climate change on drainage systems, water balance, and nitrate loss in the consolidated paddy fields of a humid region. Using climate projections downscaled from earth system models (NorESM2 and CanESM5) under two shared socioeconomic pathways (SSP126 and SSP585), we analyzed expected changes in temperature, precipitation, and evapotranspiration (ET) over three canola growing seasons. The DRAINMOD model, calibrated for local conditions, was used to simulate water balance and nitrate losses for two subsurface drainage systems with a drain depth (D) of 0.65 m and spacings (L) of 15 m and 30 m (D0.65L15 and D0.65L30). Results showed a projected increase in minimum and maximum temperatures by 0.66 °C and 1.0 °C, respectively, under SSP126, and by 0.74 °C and 1.5 °C under SSP585, compared to the baseline period. ET is expected to increase by 7.3% under SSP126 and 8.1% under SSP585, resulting in total ET of 312.6 mm and 334.3 mm, respectively, compared to 306.4 mm in the base period. Precipitation during the growing season is projected to increase by 181.3 mm under SSP126, but decrease by 15.7 mm under SSP585, leading to shifts in drainage intensity. Nitrate losses under the climate change scenarios are expected to decrease slightly, with total losses in the D0.65L15 system dropping from 9.13 kg ha−1 in the baseline period to 7.15 kg ha−1 under SSP585. These findings highlight the need for optimizing drainage design to manage increased ET and varying precipitation patterns, ensuring environmental sustainability in the face of climate change.